(5i)^3 = 5^3 * i^3 = 125(-i) = -125 i
Then :
By coefficients comparison :
a=0
b=-125
2006-09-12 06:44:05
·
answer #1
·
answered by jmdanial 4
·
1⤊
0⤋
in general, you can express 5i as 5(cos90 + i sin 90)
using the theorem, (5i)^3 = 5^3(cos270+i sin270) = -5i, meaning that there is no real part in the solution
you can do this problem simply as: (5i)^3 = 5^3 * i^3 = 5^3 * -i = -125i
2006-09-12 13:46:42
·
answer #2
·
answered by m s 3
·
1⤊
0⤋
(5i)^3 = -125i
a+bi form is: 0-125i
2006-09-12 15:29:20
·
answer #3
·
answered by bruinfan 7
·
0⤊
0⤋
a=0 and b=-125
so 0+(-125)i
2006-09-12 13:51:16
·
answer #4
·
answered by raj 7
·
1⤊
0⤋
In your book
2006-09-12 13:41:17
·
answer #5
·
answered by Anonymous
·
0⤊
1⤋
First, you have to re-route your binomials in order to properly defernilate the cirramulus. Duh.
2006-09-12 13:43:27
·
answer #6
·
answered by Anonymous
·
0⤊
1⤋